Clinical and biochemical effects of gamma-vinyl Gaba in tardive dyskinesia. Issue 12 (December 1987) - Gaio, J M; Pollak, P; Hommel, M; Perret, J
Abstract : Clinical and biochemical effects of Gamma-vinyl-Gaba (GVG) have been evaluated in a blind video-controlled study in 10 psychiatric patients (mean age 71 yr) with tardive dyskinesia. CSF free and total Gaba and homocarnosine concentrations increased from three to five fold with GVG treatment. Despite the GVG-induced biological effects on Gaba metabolism, GVG did not consistently improve tardive dyskinesia. Psychomotor side-effects occurred in older patients, who only tolerated GVG dosages of 2-4 g/day.